PUBLIC ADMINISTRATION OF PERSONAL FULFILLMENT IN SPORTS: SOCIO-PHILOSOPHICAL ASPECT - Rybchych I.Ye. (Pressing Problems of Public Administration, 2015)
The phenomenon of sports as a tool for communication and socialization in the system of public-authority relations has been researched. The purpose of sports to motivate people to disclose their essential forces has been studied. The main aspects of public administration process of getting people involved in athletic sporting activities have been found out.